2018
DOI: 10.4324/9781315147895
|View full text |Cite
|
Sign up to set email alerts
|

Governing Environmental Conflicts in China

Abstract: a million premature deaths each year. China is the world's largest emitter of carbon dioxide, and choking smog in cities reaches levels that make it hazardous to go outside. 3 According to the Ministry of Environmental Protection of China's figure for 2010, 4 the cost of pollution has reached about 1.5 trillion RMB, or roughly 3.5 percent of GDP. For the Chinese state, one unanticipated outcome caused by degrading environmental quality is the occurrence of a large number of environmental conflicts. Since 1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 179 publications
0
25
0
Order By: Relevance
“…It is found that Chinese deputies have been active in environmental bill submissions in recent years (Kamo & Takeuchi, 2012) since climate change has become a major concern among citizens and government officials (Li, 2017;Li et al, 2017;Zheng & Kahn, 2017;Zhu & Wu, 2017). There are similar or greater concerns among citizens and government officials when an environmental accident occurs, which may motivate deputies to submit bills to address the concerns and convince the local leaders that they perform their official role assignment and are worthy of reappointment.…”
Section: Bill Submissionmentioning
confidence: 99%
“…It is found that Chinese deputies have been active in environmental bill submissions in recent years (Kamo & Takeuchi, 2012) since climate change has become a major concern among citizens and government officials (Li, 2017;Li et al, 2017;Zheng & Kahn, 2017;Zhu & Wu, 2017). There are similar or greater concerns among citizens and government officials when an environmental accident occurs, which may motivate deputies to submit bills to address the concerns and convince the local leaders that they perform their official role assignment and are worthy of reappointment.…”
Section: Bill Submissionmentioning
confidence: 99%
“…High-level officials at the district, municipal, provincial, and national tiers of government are not chosen by an electorate but evaluated through an official assessment system administered from above. In this a variety of indicators play a role, of which growth of Gross Domestic Product, avoiding riots and revolts, some environmental norms and, increasingly, demonstrated loyalty to the leadership play key roles [83,84]. This evaluation is partly objectified, but it has been shown to have a variety of weaknesses including responsibility borne for duties that cannot be practically fulfilled and political (ab)use [85].…”
Section: Mobilization Of Bias Ii: Power Accumulation In Sustainable Pmentioning
confidence: 99%
“…Power accumulation has shifted to those societal groups that live in the wealthy and large cities by the East coast, where a history of party loyalty has conflated with success in government, business, or leading universities in the nation and where track records of being directly or indirectly in charge of constituencies with faster than average economic growth has been recorded over the years, where major social revolt is prevented and where the ecological discourse reflected in the use of green city labels is convincingly vented to the outside world and helps attract and keep satisfied investors, high tech corporations, talented residents, and substantial numbers of visitors [8,81,84]. As in the case of capital accumulation in sustainable urbanization, the mobilization of bias promoted through power accumulation is systematic and exceeds the thresholds of pluralistic input to decision-making or even the position of a limited number of policy actors having structurally more resources in and input to the policy process [80,94,96,99].…”
Section: Mobilization Of Bias Ii: Power Accumulation In Sustainable Pmentioning
confidence: 99%
“…This regulation was made without the participation of the other stakeholders, and most citizens complained that it was difficult to meet. Moreover, this governance style implies that different stakeholders involved in governance processes insist on their own goals and do not take others' interests seriously (Li, 2018). In the governance of home sharing, the platforms sometimes do not carefully implement the background check policy issued by local governments.…”
Section: Strategies and Styles For Governing Sharing Economy Initiativesmentioning
confidence: 99%